Climate Change Impacts on Agricultural Yields - Müller, Christoph (Washington, DC: World Bank, 2012)
Projections of future crop yields are highly uncertain. At global to regional scale, CO2 fertilization has the potential to generally increase crop yields on current crop land. However, it is highly unlikely that yield increases due to CO2 fertilization will be fully achieved in most regions, as long term positive effects are subject to scientific debate and increased yield levels require also adaptations in management. Differences in climate patterns are a major source of uncertainty in local and national yield projections, as especially precipitation patterns differ considerably between GCMs. The range of modeled impacts on yields therefore is only an indication on the locations susceptibility to climate change and for the necessity of adaptation measures. Future food demand will only be met if improved management and technological change will be able to increase crop yields considerably or if agricultural land is expanded. Even the most optimistic projections on future crop yields lead to decreasing food self-sufficiency ratios in most regions.